Serum albumin level during intestinal exfoliative rejection: a potential predictor of graft recovery and patient outcome - Zambernardi König, María Agustina (2013)
Exfoliative rejection is a severe complication after intestinal transplant. The assessment of mucosa histology is restricted to the area reached by endoscopy. We aim to evaluate the serum albumin (SA) value as a parameter of graft damage and clinical prognosis in intestinal exfoliative rejection (ExR). The present study is a retrospective analysis of 11 episodes of ExR occurred in a cohort of 26 patients. SA levels were measured 24 h after diagnosis and twice a week thereafter and then correlated with parameters of clinical and graft histological recovery (HR). During ExR, all patients had very low SA levels, reaching a minimum average of 1.9 0.3 g/dL. According to the value of albumin levels at ExR diagnosis, the patients were grouped finding a correlation with their clinical evolution. Six ExR episodes presented with severe hipoalbuminemia (<2.2 g/dL; p < 0.05) that correlated with worse patient and graft outcome, ranging from graft loss and need for retransplantation to delayed clinical and HR. SA at ExR diagnosis may be an indicator of the severity of the ExR process, and it could also be used as an early predictor of patient and graft outcome.